RESTING ELECTROCARDIOGRAPHY IN 12 COMMON LEADS: THE PRESENT AND THE FUTURE - E. V. Zemtsovsky; S. A. Abdalieva; M. F. Balluzek; A. V. Kim; N. N. Morozova (Российский кардиологический журнал, 2015)
The method of electrocardiography registration in resting state (in the following: ECG resting) in 12 common leads is considered as a routine method, that is used by a broadest range of indications for screening, in outpatient practice and standard clinical assessment of patients with various nosologies in inpatient practice. The method poor sides are discussed, i.e. a necessity for the use of heavy device, usage of the paper line, special archiving for storage and dynamics analysis. The benefits of internet-electrocardiography are shown that make it useful to record ECG by low-weight device (300 g), possibilities for ECG storage in personal space of the user, comfortable software of ECG comparison, that were recorded in dynamics.